PHYTOEXTRACTION POTENTIAL OF VETIVERIA ZIZANIOIDES ON HEAVY METALS - Aremu, Mujidat Omolara; Ogundola, Abike Funke; Emmanuel, Oyebamiji Tolulope (European Scientific Journal, ESJ, 2013)
Excessive release of heavy metals into the environment as a result of massive urbanization and industrialization has posed a great threat worldwide. In view of this, a more effective, sustainable, renewable and environmental friendliness technique is needful to curb the resulting environmental pollution. Several methods or technologies have been developed over the years for treating contaminated sites, but the kinetics of uptake of heavy metals which are necessary for the design of the treatment system have been largely neglected. This work therefore studies the uptake kinetics of three heavy metals (Lead, Zinc and Cadmium) by the plant Vetiveria zizanioides (vetiver) from contaminated soil. The model was based on bioaccumulation factors and half-life study of the heavy metals in the soil for a period of three months. From the result of the study, bioaccumulation factor (BAF) for Cadmium was found to be the minimum (0.2051mg/mg), followed by Lead (0.8265mg/mg) while that of Zinc was the maximum (0.9016 mg/mg). Also, the half- life was estimated to be 6.4 months for Zinc, 7.2 months for Lead and 29.64 months for Cadmium.